Seven theaters in search of revenue : a study of pricing strategies in the arts sector - Rindler, Rebecca M., (SAGE knowledge. Cases., 2016)
How much should tickets to Saturday night's show cost? Theatres weigh a number of concerns when deciding how to set admission prices. This study explains the complex considerations that theatres need to factor in when arriving at their admission fees.